Orthogonal precoding with memory for sidelobe suppression in OFDM - Khawar Hussain; R. López-Valcarce (European Signal Processing Conference (EUSIPCO), 2022)
Orthogonal precoding is a very effective approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. This is achieved at the cost of introducing precoder redundancy, which results in throughput loss. Introducing memory in the precoding operation has the potential to improve performance without sacrificing additional spectral efficiency, in exchange for extra computational complexity. We present a novel orthogonal memory precoder which minimizes OBR within a user-selectable frequency region and allows for controlling spectral overshoot. Decision-feedback decoding avoids symbol error rate degradation at the receiver.
Keywords: rodin; spectrum shaping